2021
DOI: 10.3390/antiox10020177
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 as a Pharmacological Target for Host-Directed Therapy to Limit Tuberculosis Associated Immunopathology

Abstract: Excessive inflammation and tissue damage are pathological hallmarks of chronic pulmonary tuberculosis (TB). Despite decades of research, host regulation of these clinical consequences is poorly understood. A sustained effort has been made to understand the contribution of heme oxygenase-1 (HO-1) to this process. HO-1 is an essential cytoprotective enzyme in the host that controls inflammation and oxidative stress in many pathological conditions. While HO-1 levels are upregulated in animals and patients infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 119 publications
(186 reference statements)
0
5
0
Order By: Relevance
“…Functionally, HO-1 catalyzes the degradation of oxidant heme into biliverdin, iron, and carbon monoxide (CO) (Szade et al, 2021). HO-1 was significantly upregulated in TB patients and in experimental animals infected with Mtb, and was a potential target for HDT for TB (Chinta et al, 2021;Uwimaana et al, 2021). In the present report, the increase of both HO-1 protein and Hemin content, a main source of iron for Mtb and host cells, was also observed in peripheral blood of TB patients, at both transcriptional and/or translational levels, which was strongly correlated with several cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionally, HO-1 catalyzes the degradation of oxidant heme into biliverdin, iron, and carbon monoxide (CO) (Szade et al, 2021). HO-1 was significantly upregulated in TB patients and in experimental animals infected with Mtb, and was a potential target for HDT for TB (Chinta et al, 2021;Uwimaana et al, 2021). In the present report, the increase of both HO-1 protein and Hemin content, a main source of iron for Mtb and host cells, was also observed in peripheral blood of TB patients, at both transcriptional and/or translational levels, which was strongly correlated with several cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the increase of apoptosis is correlated with a reduced ferroptosis needs further study. ROS generated from lipid peroxidation is crucial in cell ferroptosis (Conrad et al, 2018), and HO-1 is an essential cytoprotective enzyme that inhibits inflammation and oxidative stress (Araujo et al, 2012;Rockwood et al, 2017;Seiwert et al, 2020;Chinta et al, 2021;de Oliveira et al, 2022), and a target for HDT of TB (McLean and Munro, 2017;Chinta et al, 2021). The expression of HO-1 is largely dependent on oxidative stress in Mtb-infected cells, where an elevated expression of HO-1 is a strategy of host cells in response to oxidative stress triggered by intracellular bacteria (Rockwood et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 exerts anti-inflammatory and cytoprotective effects, although the underlying mechanisms are not fully understood (196). Several studies have investigated the host beneficial or detrimental roles of HO-1 during TB infection (95,99,(192)(193)(194)(195). Andrade et al showed that active TB patients show a negative correlation between plasma levels of HO-1 and MMP-1 (95).…”
Section: Ho-1 Inhibitormentioning
confidence: 99%
“…In section 3, we discussed that Mtb and bactericidal anti-TB drugs cause mitochondrial dysfunction and oxidative damage in host cells, consequently ROS-mediated apoptosis as well as simultaneous activation of antioxidant mechanisms, such as the Keap1-Nrf2 signaling pathway, that may interfere with the removal of Mtb ( 88 , 89 ) A major factor involved in this mechanism is HO-1 ( 95 , 192 ). However, the detailed role of host HO-1 during the onset and pathogenesis of TB remains controversial and has not been fully elucidated ( 95 , 99 , 192 195 ). HO-1 exerts anti-inflammatory and cytoprotective effects, although the underlying mechanisms are not fully understood ( 196 ).…”
Section: Adjunctive Host-directed Therapies Improve Anti-tb Drug Activitymentioning
confidence: 99%
See 1 more Smart Citation